Gestión de las cuentas por cobrar de la Empresa Agroswer de la parroquia Ricaurte cantón Urdaneta durante el periodo 2022-2023. - Encalada Castillo, Nayely Yulady (2024)
The investigation was carried out in the Agroswer company of the Ricaurte parish of the Urdaneta canton, where the management of accounts receivable is investigated, because the organization studied experienced a significant increase in the collection rights acquired in making sales.; Therefore, the general objective of the study was proposed: Examine the management of accounts receivable of the Agroswer Company during the period 2022-2023. The methodological framework is made up of a mixed, qualitative and quantitative approach, while the types of research were: field and documentary; In addition, the techniques implemented are the interview and documentary analysis, which allowed obtaining relevant findings on the analysis of accounts receivable, such as: the company does not have a collection management manual, which causes the absence of credit policies. clear ones that help improve the behavior of the account analyzed; Likewise, it was determined that, despite the increase in accounts receivable, this has not yet significantly affected the business financial situation. Therefore, collection management is carried out empirically and technical controls on the behavior of accounts pending collection are omitted.